Information, Power, and Politics: Technological and Institutional Mediations - Albagli, Sarita; Maciel, Maria Lucia (Lexington Books, 2010)
With the spread of information and communication technologies (ICTs) comes the potential both for new social and economic equalities and new forms of inequalities. Information, Power, and Politics: Technological and Institutional Mediations demonstrates that ICTs can act as an impetus for democratizing information and knowledge, while at the same time new institutional frameworks can limit one's use of and access to strategic information and knowledge. The volume's contributors address ways to strengthen and affirm the socially marginalized as well as suggest how best to incorporate (semi)peripheral countries and regions into the international system. Information, Power, and Politics offers a refreshing and timely perspective on the ever-evolving relationship between information, knowledge, and communication.